A conserved Zn2Cys6 transcription factor, identified in a spontaneous mutant from in vitro passaging, is involved in pathogenicity of the blackleg fungus Leptosphaeria maculans. Issue 7 (July 2021) - Chambers, Kylie R.; Van de Wouw, Angela P.; Gardiner, Donald M.; Elliott, Candace E.; Idnurm, Alexander
Abstract: Continuous passaging in vitro can lead to the accumulation of changes in DNA sequence that potentially affect the properties of microbes, making them different from the original isolates. The identification of such genetic alterations is rare in fungi. A set of insertional mutants in the plant pathogenic fungus Leptosphaeria maculans, all derived from the same transformation experiment, had independent Agrobacterium T-DNA insertions and reduced pathogenicity on canola ( Brassica napus ). None of the insertions co-segregated in progeny from crosses with the reduction in pathogenicity. Genome sequences of three strains were analysed, and a mutation identified in a gene ( ptf1, for pathogenicity-associated transcription factor 1) encoding a putative Zn2 (II)Cys6 transcription factor. Homologs are found in other ascomycetes, and are required for pathogenicity by Fusarium graminearum, Fusarium oxysporum and Magnaporthe oryzae . The mutation in the L. maculans ptf1 gene co-segregates in progeny from crosses with the reduction in pathogenicity, a strain with an independent mutant allele isolated using CRISPR-Cas9 editing has reduced pathogenicity, and addition of wild type copies of the gene restores pathogenicity. Thus, this work defines a base pair substitution that occurred during in vitro passaging of a fungus that contributed to an attenuation of pathogenicity. Highlights: Fungal strains from the same transformation experiment had reduced pathogenicity. T-DNA insertion were not responsible for reduced disease. Point mutations were found in a new gene, ptf1, in Leptosphaeria maculans . ptf1 encodes a transcription factor conserved in other plant pathogens. The basis behind mutations during in vitro culture can be identified in fungi.